Pengaruh Leverage, Financial Distress dan Profitabilitas terhadap Konservatisme Akuntansi pada Perusahaan Pertambangan di Indonesia Tahun 2013-2017 - Abdurrahman, Muhammad Affan; Ermawati, Wita Juwita (IPB University, 2018)
Accounting conservatism is a precautionary principle in reporting financial statements. This principle slows down the recognition of income and accelerates the recognition of costs, resulting in low profits and assets, and high costs and debt. This study aims to analyzing the effect of leverage, financial distress and profitability as independent variable to accounting conservatism in mining companies as dependent variable. The sample of this study used 20 listed companies. This research are using secondary data published by the company and BEI. Methods in this study using multiple regression analysis processed with software Eviews 10. The results showed that independent variables together significantly affect the changes in accounting conservatism. Profitability variables have a negative and significant effect on accounting conservatism of mining companies.